Selectivity of Cobalt Corrole for CO vs. O(2) and N(2) in Indoor Pollution - Sheng, Xia (Sci Rep, 2017)
Coal combustion causes indoor pollution of CO. In this work, DFT calculations on cobalt corrole (Co(Cor)) with three most common indoor gas molecules (N(2), O(2) and CO) were performed. The Mulliken spin densities show that the ground states of Co(N(2))(Cor), Co(CO)(Cor) and Co(OC)(Cor) have an anti-ferromagnetic coupling fashion of the electrons on the Co 3d (z) (2) orbital and the π orbital of the corrole ring. However, Co(O(2))(Cor) has a triplet ground state. With the spin contamination corrections, the Co(N(2))(Cor) binding energy was obtained at −50.6 kcal mol(−1) (B3LYP-D3). While CO can interact with Co(Cor) in two different ways, and their binding energies were −22.8 and −10.9 kcal mol(−1) (B3LYP-D3) for Co(CO)(Cor) and Co(OC)(Cor), respectively. The natural bond orbital charges on the axial ligands (NO, CO, OC) are increased upon the chemical bond formation. These are the cause of the shorten metal-ligand bond and the increase of the wavenumber of the metal-ligand bond vibrational transitions. While the charges for O(2) are decreased, leading to bond elongation as well as the decrease of the wavenumber upon complexation. Overall, O(2) was found to be hardly coordinated with Co(Cor). This study provides a detailed molecular understanding of interactions between a gas sensor and gaseous indoor air-pollutants.